Fluctuation of main insect pests and diseases in cañihua (Chenopodium pallidicaule Aellen) of the Peruvian Andean Altiplano - Leon Ttacca, Betsabe; Bravo Portocarrero, Rosario; Llanos Nina, Joven; Leon Tacca, Alicia; Medina Espinoza, Wenceslao (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The Andean crop germplasm bank, of the Camacani Experimental Center of the Universidad Nacional del Altiplano de Puno, has around 400 accessions of cañahua (Chenopodium pallidicaule Aellen), and 27 of them have been agronomically characterized. Given the importance of this crop for the inhabitants of highlands of the Peruvian Andes, the objective of this research was to assess the population fluctuation of insect pests and the severity of diseases in the mentioned accessions, along with three commercial varieties. The evaluations were carried out in three phases of the crop development, including the grain yield. It was found that the accessions and varieties of cañahua were tolerant to the attack of most pests and diseases. The most important pest was Eurysacca quinoae Povolny, especially in the accession 03-21-26 and the Ramis variety, in which up to 5.5 and 4.5 larvae were found per plant, respectively; however, the pest did not exceed the economic threshold of 6 larvae per plant during the phenological phases. In regards to diseases, it was confirmed that Peronospora sp. (mildew) is the main pathology that occurred during the agricultural season. Accessions 03-21-03 and 03-21-24 were not affected by the disease, while accessions 03-21-267, 03-21-218, 03-21-124, 03-21-26 and 03-21-64 were the most affected, showing the highest severity and area under the disease progress curve.  When evaluating one season, the accessions and varieties of cañihua showed resistance to insect-pests and diseases, without appreciably decrease of their grain yields.